2014
DOI: 10.1177/1052562914560794
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Failure as a Threshold Concept

Abstract: Some curricular elements are threshold concepts that involve "troublesome knowledge," not because they are difficult for students to comprehend per se, but because they are challenging for students to fully appreciate. In this article, we suggest that entrepreneurial failure is a threshold concept in entrepreneurship courses because students may get so fixated on failure's economic costs that they neither fully appreciate the social and emotional costs nor recognize the potential benefits of failure to entrepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 68 publications
0
31
1
2
Order By: Relevance
“…Firstly, internal motivation means that the individual has an internal need of establishing a set of new methods after failure, and such need will help them learn the failure more effectively. Secondly, the individual' s past experience of failure will influence the next learning behavior from failure [18], and students with entrepreneurial experience have a deeper understanding about failure [19]. As for reflections of the influence of such past experience on learning from failure at micro psychological level, self-adjustment and self-leadership of the individual can help people recover from failure quickly; moreover, the psychological sense of security at individual level will influence learning from failure in the entire organization [20].…”
Section: Influence Factors At Individual Levelmentioning
confidence: 99%
“…Firstly, internal motivation means that the individual has an internal need of establishing a set of new methods after failure, and such need will help them learn the failure more effectively. Secondly, the individual' s past experience of failure will influence the next learning behavior from failure [18], and students with entrepreneurial experience have a deeper understanding about failure [19]. As for reflections of the influence of such past experience on learning from failure at micro psychological level, self-adjustment and self-leadership of the individual can help people recover from failure quickly; moreover, the psychological sense of security at individual level will influence learning from failure in the entire organization [20].…”
Section: Influence Factors At Individual Levelmentioning
confidence: 99%
“…When students do not address the issue of failure in EE, they are prevented from developing a realistic and balanced perspective of entrepreneurship. Without understanding the prevalence of failure (as well as how to prevent it or mitigate the ensuing consequences), students are sub-optimally prepared for an entrepreneurial career (Bolinger and Brown 2015). Learning how to prepare for and deal with adversity and failure is likely to reduce psychological, social and economic losses, and enable entrepreneurs to recover faster and re-embark on their entrepreneurial path (Shepherd 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, this study contributes to the scientific debate about EE in general (Matthews 2018;Nabi et al 2017) by moving beyond the traditional focus on starting, growing and succeeding in a particular area, and by incorporating strategies for dealing with and becoming resilient in the face of adversity and failure. Specifically, the study expands the scant literature on learning from failure (Bolinger and Brown 2015;Shepherd 2004) by examining the lessons that students have learned from interviewing entrepreneurs about their 'experiences of failure'.…”
Section: Introductionmentioning
confidence: 99%
“…Entrepreneurs and scholars are more prone to seek constructive information from successful cases rather than failed experiences ( Ellis and Davidi, 2005 ). Recently, with the vanishing of a stable environment, researchers have started to shift emphasis from learning from successful experiences to failed experiences ( Kapur, 2008 ; Potter, 2013 ; Bolinger and Brown, 2015 ; Simpson and Maltese, 2017 ). This can provide more valuable information and can prevent individuals or organizations from failing again for the same reason ( Ford, 1999 ; Labib and Read, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, Shepherd (2003) proposes that people may not always take proactive measures (e.g., learning) after failure, but become obsessed with failures or show avoidance behavior, calling for the need to exploring the antecedents of learning from failure. Past studies have found that personal traits and experiences exert a considerable influence on an individual’s behavior after failures ( Boss and Sims, 2008 ; Bolinger and Brown, 2015 ). For instance, Boss and Sims (2008) find that self-leadership can help individuals move toward recovery.…”
Section: Introductionmentioning
confidence: 99%